2017
DOI: 10.1007/s12010-017-2536-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Conversion of Fructose-Based Biomass into Lipids with Trichosporon fermentans Under Phosphate-Limited Conditions

Abstract: Limiting nitrogen supply has been routinely used as the master regulator to direct lipid biosynthesis. However, this strategy does not work with nitrogen-rich substrates, such as Jerusalem artichoke (JA), a fructose-based biomass, while it is difficult to obtain a high carbon-to-nitrogen (C/N) molar ratio. In this study, an alternative strategy to promote lipid accumulation by the oleaginous yeast Trichosporon fermentans CICC 1368 was developed by limiting phosphorous supply, and this strategy was implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…These results showed that cells had lipids less that 10% without nutrient limitation, while cells accumulated lipids to over 40% under Pi-limitation. Our data were in agreement with a number of earlier observations that Pi-limitation facilitated lipid production by oleaginous fungi [ 6 , 8 10 ]. More interestingly, the much greater increase in lipid yield than in cell mass yield suggested that cells used glucose more efficiently for lipid biosynthesis under Pi-limitation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results showed that cells had lipids less that 10% without nutrient limitation, while cells accumulated lipids to over 40% under Pi-limitation. Our data were in agreement with a number of earlier observations that Pi-limitation facilitated lipid production by oleaginous fungi [ 6 , 8 10 ]. More interestingly, the much greater increase in lipid yield than in cell mass yield suggested that cells used glucose more efficiently for lipid biosynthesis under Pi-limitation.…”
Section: Resultssupporting
confidence: 93%
“…As Pi can be readily removed from aqueous streams at large scale, it is appealing to use Pi-limitation as a convenient strategy to explore nitrogen-rich raw materials for lipid production. Indeed, high cellular lipid contents were documented by different oleaginous hosts under Pi-limitation [ 8 10 ], even in the presence of excess nitrogenous nutrients [ 7 , 11 ]. Nonetheless, the molecular basis of cellular responses to Pi-limitation and concurrent lipid accumulation by oleaginous species remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid (C18:1) was only be detected at low levels in sugar-based media and was not detected after incubation with glycerol (Shen et al 2015). Three major fatty acids of the same strain of oils obtained from medium with fructose were palmitic acid (16:0), stearic acid (18:0), and oleic acid (18:1), and these three fatty acids accounted for over 95% of the total fatty acids (Bao et al 2018).…”
Section: Biomass Yield and Lipid Contentmentioning
confidence: 98%
“…The enzyme has an optimum pH in the range of 8.0-8.5 and an optimum temperature of 32°C and shows no metal dependence on the chloride salts of sodium, potassium, magnesium, or ferrum (Goldson-Barnaby and Scaman 2013). Trichosporon fermentans can produce lipids with various cheap substrates such as rice straw hydrolysates (Huang et al 2009) and molasses (Zhu et al 2008;Shen et al 2015) or nitrogen-rich Jerusalem artichoke hydrolysates (Bao et al 2018). T. cutaneum produces biomass rich in oils after incubation on steam-exploded and three-stage enzymatic hydrolysis corn stover.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble phosphate can be removed by precipitation with metal ions, such as Ca 2+ and Mg 2+ (Kolouchová et al 2016). Treatment with Ca(OH)2 (over-liming) is a popular method for removing soluble phosphate by precipitating it as Ca3(PO4)2 (Xia et al 2016;Bao et al 2018). This approach has been used to remove phosphate from several lignocellulosic hydrolysates (Wu et al 2010;Bao et al 2018;Zhou et al 2019).…”
Section: Maximization Of the Oil Production By Cy Subsufficiens Ng82 In 12%-slhmentioning
confidence: 99%